2020
DOI: 10.3390/ma13102272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Optimization of TiO2 Electron Transport Layer on Performance of Perovskite Solar Cells with Rough FTO Substrates

Abstract: The film quality of the electron transport layer (ETL) plays an important role in improving the performance of perovskite solar cells (PSCs). In order to reduce the effect of rough fluorine-doped SnO2 (FTO)substrate on the film quality of the TiO2 ETL, multiple cycles of spin-coating were employed to realize optimized TiO2 film and improve the performance of PSCs with rough FTO. The results show that TiO2 ETL was optimized most effectively using two spin-coating cycles, obtaining the best performance of PSCs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…The fourth perovskite film (Film D) was grown on the mesoporous TiO 2 layer (FTO/ALD-TiO 2 /mp-TiO 2 /perovskite). It can be seen that the morphology of the perovskite films and grain sizes are similar and the surfaces are flat and smooth, in agreement with other reports elsewhere [23,32].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The fourth perovskite film (Film D) was grown on the mesoporous TiO 2 layer (FTO/ALD-TiO 2 /mp-TiO 2 /perovskite). It can be seen that the morphology of the perovskite films and grain sizes are similar and the surfaces are flat and smooth, in agreement with other reports elsewhere [23,32].…”
Section: Resultssupporting
confidence: 91%
“…The fourth perovskite film (Film D) was g the mesoporous TiO2 layer (FTO/ALD-TiO2/mp-TiO2/perovskite). It can be seen morphology of the perovskite films and grain sizes are similar and the surface and smooth, in agreement with other reports elsewhere [23,32]. The cross-sectional SEM images of the same perovskite films are shown in It is seen that the morphology and grain distribution in the films grown on the TiO2 are similar (Figure 5a,c).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Although organic materials have good solubility in the treatment process, their low electron mobility and high cost hinder the commercialization of PSCs. Inorganic materials, especially metal oxides [6][7][8][9][10][11][12][13][14][15][16][17][18], are endowed with superior advantages of low cost, high stability, and excellent photoelectric property [12,19,20], are usually used as electron transport layer materials.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxides such as TiO 2 [6][7][8][9], ZnO [14,15], and SnO 2 [10][11][12][13][14]21], have become the mainstream materials of ETLs. Giordano and co-workers have demonstrated that the electronic trap states could be reduced and electron transport could be enhanced by introducing Li-ions into TiO 2 ETLs [22].…”
Section: Introductionmentioning
confidence: 99%